Terapi periodontal non-bedah Non-surgical periodontal therapy - Liana Zulfa; Dewi Nurul Mustaqimah (Journal of Dentomaxillofacial Science, 2011)
Non surgical periodontal therapy is the first step in periodontal therapy procedure. Elimination of biofilm andmineral deposit from tooth surface is a basic of periodontal therapy. Clinical data showed that the success of longterm periodontal therapy depends on the result of first step compare to spesific surgical therapy. Methods used innon surgical therapy are mechanical instrumentation, ultrasonic debridement, supragingival and subgingivalirigation, localized drugs, systemic antibiotics, and host response modulation. The successful of periodontal therapydepends on the management of negative environment and reduction of bacterial pathogen through a combination ofbetter environment which is less anaerobic for good microorganism to live. The aim of non surgical therapy is toreduce microbial etiology and factors involved in the progression of gingiva and periodontal. The end result is tostop the disease progression and to gain healthy gingiva and tissue condition.